Measuring Stakeholder Integration: Knowledge, Interaction and Adaptational Behavior Dimensions - Plaza-Úbeda, José A. (Journal of business ethics, 2010)
Stakeholder Theory combines the pursuance of business goals and responsibility toward a firm’s stakeholders. Despite the wealth of research on Stakeholder Orientation, we still have much to learn about specific measurements for several related constructs. In this study, we draw on two samples of 129 and 151 Spanish firms, respectively, to investigate CEOs’ perceptions on Stakeholder Integration (SI), leading to the identification of three dimensions of the construct. In this respect, our study suggests that Knowledge of Stakeholders, Interactions between a firm and its stakeholders, and the adaptation of a firm’s behavior to stakeholders’ demands constitute the main dimensions of SI. This construct has the potential to connect the stakeholder and strategy literatures.